Fractional optical normalization operator of magnetic field and electroosmotic optimistic energy - Ogrenmis, Meltem (Springer, 2024)
In this manuscript, we introduce optical fractional normalization and fractional recursive operators for a particle. The significance of this research lies in obtaining optical fractional recursive operators and normalized operators of magnetic fields through the utilization of a fractional spherical frame within spherical space. Throughout the study, we employ the general form of fractional derivatives, as it enables us to derive more generalized results compared to classical derivatives. Additionally, we derive the microfluidic optical fractional electroosmotic magnetic optimistic fractional energy. We propose a design for optical recursion-based fractional electroosmotic magnetic optimistic fractional energy. This innovative study holds significant potential for applications across various fields, including fluid dynamics, optics, and energy conversion.
Keywords: Normalization operator; Optical fractional normalization; Microfluidic microscale; Recursive optimistic density